Cell Proliferation in the Adult Chicken Hippocampus Correlates With Individual Differences in Time Spent in Outdoor Areas and Tonic Immobility - Armstrong, Elena A.; Voelkl, Bernhard; Voegeli, Sabine; Gebhardt-Henrich, Sabine G.; Guy, Jonathan H.; Sandilands, Victoria; Boswell, Tim; Toscano, Michael J.; Smulders, Tom V. (Frontiers in Veterinary Science, 2020)
Access to outdoor areas is provided as a means of enhancing welfare in commercial systems for laying hens (Gallus gallus domesticus), but substantial individual differences exist in their proportional use. Baseline cell proliferation levels of Adult Hippocampal Neurogenesis (AHN) have been associated with individual differences in reactive versus proactive coping style, and in both mammals and birds, AHN is upregulated by positive experiences including environmental enrichment and exercise. We thus sought to explore whether individual differences in use of outdoor areas and in tonic immobility responses (indicative of fearfulness) were associated with hippocampal cell proliferation and neuronal differentiation. Radio frequency identification technology was used to track the ranging behaviour of 440 individual focal hens within a commercially-relevant system over a 72-day period, after which tonic immobility durations were measured. Following hippocampal tissue collection from 58 focal hens, proliferation and neuronal differentiation were measured through quantitative PCR for proliferating cell nuclear antigen (PCNA) and doublecortin mRNA respectively. Individual differences in tonic immobility duration positively correlated with PCNA expression over the whole hippocampal formation, while greater time spent in outdoor areas (the grassy range and stone yard) was associated with higher proliferation in the rostral subregion. Basal proliferation in the chicken hippocampal formation may thus relate to reactivity, while levels in the rostral region may be stimulated by ranging experience. Doublecortin expression in the caudal hippocampus negatively co-varied with time on the grassy range, but was not associated with tonic immobility duration. This suggests that ranging outside may be associated with stress. Within laying hen flocks, individual differences in hippocampal plasticity thus relate to coping style and use of external areas.